Wegeners Granulomatosis Mimicking Pulmonary (Journal of Bangladesh College of Physicians and Surgeons, 2012)
Wegeners Granulomatosis(WG) is a rare type of multisystem small to medium vessel vasculitis with necrotizing granulomatous inflammation involving the upper airway, lungs and the kidneys. In generalized WG, patient invariably dies within few months if left untreated. The key to better prognosis is early treatment once the diagnosis is made. Our patient is a 21yr young lady who was initially diagnosed as nasal septal abscess and later as pulmonary tuberculosis. She was treated accordingly but did not improve. When presented to us, she had asymmetric polyarthritis, cough with mucoid expectoration, intermittent mild haemoptysis as well as fever with bilateral nasal obstruction and epistaxis of about 2 months duration. She was found to have saddle nose deformity with blocked nasal passage and easily bleeding nasal crusts. Bilateral episcleritis and oral aphthous ulceration were also present. Chest X-Ray showed bilateral consolidations and infiltrates. Her hemoglobion was 6.42 gm% with high ESR and CRP. Microscopic haematuria with high serum creatinine and strongly positive C-ANCA were also found. MRI showed rt maxillary sinusitis and right mastoiditis. Finally she was diagnosed as diffuse Wegeners Granulomatosis according to ACR criteria. She was put on oral cyclophosphamide and prednisolone with satisfactory response on follow up.   DOI: http://dx.doi.org/10.3329/jbcps.v30i2.11419   J Bangladesh Coll Phys Surg 2012; 30: 98-104